The association between test anxiety, learning strategies, and open-label placebo effects on academic test performance: a secondary analysis of a randomized controlled trial - Frisaldi, Elisa; Kleine-Borgmann, Julian; Hartmann, Helena; Benson, Sven; Bingel, Ulrike; Schmidt, Katharina (Frontiers in Psychology, 2025)
IntroductionThe management of educational stressors and predictors of cognitive performance outcomes, such as test anxiety and learning strategies (LS), pose relevant challenges for students and educators. In a previously published single-blind randomized controlled trial (DRKS00013557), we reported on the impact of a 3-week open-label placebo (OLP) treatment compared to no intervention on results of a central examination and subjective well-being in healthy medical students. OLP treatment had a positive effect on students' subjective well-being, and test performance was better in those students in the OLP group with higher beliefs in benefits of medication. The present secondary analysis, conducted on a subgroup of the main study, aimed to explore whether further potential factors of exam performance influenced the impact of OLPs intake on cognitive outcomes.MethodsThis secondary analysis investigated a subgroup of the main study's sample (N = 104) in which learning strategies were assessed. Here, we conducted an explorative analysis to investigate the effects of test anxiety, LS, and 3-week OLP intake on test performance.ResultsOLP intake compared to no intervention was associated with improved test performance in those students with higher levels of test anxiety and those who adopted beneficial LS.DiscussionThese findings provide preliminary evidence that psychological processes, such as anxiety or the application of cognitive strategies, modulate the effects of OLPs on cognitive performance in exam situations, framed within the context of self-efficacy. Further pre-registered, hypothesis-driven research is warranted, as harnessing these processes in the light of OLP applications could optimize students' well-being and maximize their academic success, including long-term potential for optimizing therapeutic outcomes in clinical settings.